2004
DOI: 10.2337/diabetes.53.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to Peripherally Administered Melanocortins in Lean and Obese Mice

Abstract: To elucidate mechanisms of melanocortin action, we investigated the effects of a melanocortin receptor agonist (melanotetan II [MTII]) in lean C57BL/6J and obese (DIO, ob/ob, UCP1-DTA) mice. MTII administration (100 g q.i.d. i.p.) for 24 h results in similar weight loss but a more pronounced decrease of food intake in DIO mice. After 4 and 8 days of MTII treatment, however, the reduction in both food intake and body weight is more pronounced in DIO mice than in lean mice. MTII administration for 24 h prevents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 44 publications
4
56
0
1
Order By: Relevance
“…Activation of the central melanocortin system by MTII and other melanocortin analogues is efficacious in reducing body weight, food consumption and adiposity in animals with diet-induced obesity [21,22,24,25]. Similarly, we demonstrated that central Pomc gene delivery alleviates obesity and insulin intolerance in rats with genetic or adultonset obesity [26,27].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Activation of the central melanocortin system by MTII and other melanocortin analogues is efficacious in reducing body weight, food consumption and adiposity in animals with diet-induced obesity [21,22,24,25]. Similarly, we demonstrated that central Pomc gene delivery alleviates obesity and insulin intolerance in rats with genetic or adultonset obesity [26,27].…”
Section: Discussionmentioning
confidence: 67%
“…Such resistance renders the use of leptin futile in treating obesity in animals and humans with diet-induced obesity. On the contrary, melanotan II (MTII) and other melanocortin analogues ameliorate obesity effectively in leptin-resistant rodents [21][22][23][24][25]. Furthermore, chronic hypothalamic overexpression of Pomc by delivery of the Pomc gene via recombinant adeno-associated virus (rAAV) partially reverses the obese and diabetic phenotypes in genetically obese fa/fa (Lepr/Lepr) rats and those with adult-onset obesity [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to our data, it has been demonstrated in another experiment that elevation of liver AdipoR1 expression and reduction in the AdipoR2 expression were observed in obese mice given a combination of leptin and a melanocortin receptor agonist, although there were no alterations in the AdipoR1 or AdipoR2 expression in the mice receiving the melanocortin receptor agonist alone. 29) In addition, changes in AdipoR1/R2 expression in skeletal muscle and adipose tissue have been reported in type 2 diabetic patients during PPAR-γ agonist therapy. 30) AdipoR1 expression was up-regulated in adipose tissue but down-regulated in muscle by rosiglitazone.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a contribution of peripheral melanocortin peptides to the obesity phenotype independently of glucocorticoid secretion cannot totally be excluded from our study, since the phenotype of Pomc -/-Tg + mice in the absence of circulating corticosterone has not been evaluated. Peripheral administration of αMSH agonists has been shown to cause weight loss in mice with high-fat diet-induced obesity and genetically obese mice (65)(66)(67), and in fa/fa rats (68,69). In addition, systemic injection of [Nle 4 , D-Phe 7 ]-melanocyte-stimulating hormone reduced food intake and weight gain in Pomc -/-mice (7).…”
Section: Figurementioning
confidence: 99%